Eco-friendly management of pests and diseases in small cardamom - Soundarajan, Sudhakar; Paul, Preethu K; A, Ashiba; Marimuthu, R; Sushil, S N; Sivakumar, G; Venkatesan, T; Nagesh, M; Venkatasubramanian, V; Rayudu, B T (Indian Farming, 2024)
Small cardamom, known as 'green gold', symbolizes India's prominence in the global spice market, originating from the Western Ghats Forest in southern India. Over time, environmental changes in this region have led to indiscriminate use of synthetic chemical pesticides by farmers, resulting in environmental degradation and high pesticide residue levels in produce. As focus shifts towardsorganic small cardamom production, the search for safer pest and disease management measures becomes crucial. ICAR-National Bureau of Agricultural Insect Resources (NBAIR), Bengaluru, has developed various bio-agents effective for eco-friendly management of major cardamom pests and diseases. In the last five years, ICAR-KVK, Idukki, has extensively disseminated these technologiesamong small cardamom farmers through various activities, leading to increased adoption of ecofriendly practices, reduced pesticide usage, improved crop health, and sustainable production. With a growing demand for organic spices, ICAR-NBAIR technologies have played a pivotal role in Idukki district, enabling the production and export of safer small cardamom and its value-added products to domestic and international markets.